2017
DOI: 10.3389/fphys.2017.00152
|View full text |Cite
|
Sign up to set email alerts
|

Iodixanol as a Contrast Agent in a Fibrin Hydrogel for Endodontic Applications

Abstract: The application of biomaterials used in regenerative endodontics should be traceable. In this study, we checked some basic effects of rendering a fibrin hydrogel radiopaque using an iodine-based contrast agent (iodixanol) approved for systemic application. Fibrin hydrogels were prepared from a fibrin sealant (Tisseel) using either an isotonic iodixanol solution (Visipaque 320, test) or Tris buffer (control) as a diluent. Gelation kinetics, radiopacity, and swelling of lyophilized hydrogels were tested using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…al. [37] suggested iodixanol combined fibrin hydrogels for endodontic applications. Their ex vivo preliminary experiments in human teeth showed that the radiopacity of the fibrin hydrogels was only sufficient for correct localization of the implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [37] suggested iodixanol combined fibrin hydrogels for endodontic applications. Their ex vivo preliminary experiments in human teeth showed that the radiopacity of the fibrin hydrogels was only sufficient for correct localization of the implant.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it was indicated that the characteristics of hydrogels dramatically changed due to the addition of the iodixanol CA. [37] In this study, it was crucial to preserve the physicochemical properties of the scaffolds and their cytocompatible characteristics. Thus, among different CAs, AuNPs have been utilized as a promising candidate due to their high X-ray attenuation, depending on their size and concentration [38].…”
Section: Discussionmentioning
confidence: 99%
“…Radiopacity was determined using a standard set‐up as described previously (Hertig et al . 2017). In brief, electronic data sets were generated using a fixed unit (Trophy, Paris, France) at 65 kV, 8 mA and 0.22 s with a focus‐film distance of 25 cm and electronic sensors (Digora; Soredex, Tuusula, Finland).…”
Section: Methodsmentioning
confidence: 99%
“…The first time the allogeneic MSCs were used was to treat patients with osteogenesis imperfecta. The improvements in bone structure and function obtained were reported (Horwitz et al, 1999). Since then, MSCs have been used in a large number of different animal models and randomised clinical trials, including treatment of acute myocardial infarction, ischaemic stroke, acute kidney failure and Crohn ś disease as well as steroidrefractory acute graft-versus-host disease (acute GvHD), which arises as a side effect of allogeneic hematopoietic stem cell transplantation therapies (Giebel et al, 2017).…”
Section: Mscs and Their Therapeutical Effectsmentioning
confidence: 99%
“…Importantly, fibrin gels are commercially available clinically approved biomaterials and appear to be suitable delivery vehicles for exosomes in pulp regenerative procedures. However, additional preclinical and clinical studies are needed, especially related to their thrombin/fibrinogen composition and other physicochemical features relating to a controllable application in the root canal system (Hertig et al, 2017).…”
Section: Delivery and Matrix Systems For Pulpal Regeneration In Conjunction With Exosomesmentioning
confidence: 99%